Nationwide analysis of the relationships between mental health, body mass index and tinnitus in premenopausal female adults in Korea: 2010–2012 KNHANES - Dong-Hee Lee (Nature Portfolio, 2018)
Abstract Tinnitus is related to serious comorbidities such as suicidal ideation and attempts. Body mass index (BMI) is associated with auditory symptoms including hearing loss. The aim of this nationwide, population-based, cross-sectional study was to evaluate the relationship between mental health, body mass index and tinnitus in a Korean premenopausal female population. This study analyzed data from the Korea National Health and Nutrition Examination Surveys in 2010–2012. Data were collected from 4628 19 years or older, premenopausal women. After adjustments, underweight premenopausal women exhibited a higher odds ratio for tinnitus (odd ratio = 1.54; 95% confidence interval = 1.14–2.08) compared with women of normal weight. Moderate and severe tinnitus was highly prevalent in underweight as well as extremely obese women. The prevalence of perceived stress, melancholy, and suicide ideation was significantly higher in women with tinnitus. The prevalence of perceived stress and suicide ideation was significantly higher in underweight women with tinnitus, but that of melancholy was significantly lower. This study demonstrated that underweight premenopausal Korean women had a higher risk of tinnitus, which has grown in importance as a public health issue. Women with tinnitus experience perceived stress and suicide ideation more frequently, but melancholy less frequently than women without.